UPAYA MEMENANGKAN PERSAINGAN USAHA MELALUI WIRAUSAHA PEMASARAN/MARKETING ENTREPRENEUR - Farida, Naili (FORUM, 2012)
In today's global era entrepreneur means all product are handled itself starts from the purchase of ra materials, production processes and yield a product and proudced to be marketed to consumers, but entrepreneurial products can evolve into an entrepreneurial marketing. Entrepreneurial marketing does not have to produce their own but can take products from various product entrepreneuris and not tied to a specific product but rather an entrepreneurial free cooperation of various entrepreneurial product. Marketed products may vary from handicraft products, food, garments, artwork, creative industries from various regions, provices or even between countries that live marketing entrepreneurs to market these products. The focus of entrepreneurial marketing is not a product, but the market, entrepreneurial succes if it is able to market products to consumers and consumers to become Â customers satisfield loyal. marketing entrepreneurs is 1)risk factors received relatively small compared to entrepreneurial product and 2)the capital invested relative factor smaller than it needs to be done is 3) factors make network marketing, sample marketing entrepreneurs start finance, banking, branding, packaging and marketing channel distribution. Entrepreneur forward to spearhead improving national economy.